Effects of pH on the Nickel Coating Microstructure and Internal Stress from an Additive-Free Watts-Type Bath with Phytic Acid. Issue 11 (16th August 2018) - Zhang, Chonghui; Liu, Huicong; Ju, Pengfei; Zhu, Liqun; Li, Weiping
Abstract : The black nickel coatings were electro-deposited on Cu substrate in an additive-free Watts-type bath containing phytic acid. The function of phytic acid in the bath at different pH values on electrodeposition characteristics, surface morphology, microstructure, crystallographic orientation and grain size of nickel electrodeposits were systematically analyzed. In addition, the effects of phytic acid on deposit properties (microhardness, internal stress and plating color) were investigated. It is demonstrated that increasing pH promotes the preferred crystal orientation modification from (200) to (220) and refines grain size. With increasing the pH value, P element content increases. Under these circumstances, the internal stress reaches a minimum, the plating is the darkest and the microhardness is relatively high, when the pH is 4.5. The presence of phytic acid and appropriate pH value can lower the internal stress and get the dark nickel coatings.